Airways obstruction associated with graft versus host disease after bone marrow transplantation. Issue 12 (December 1984) - Wyatt, S E; Nunn, P; Hows, J M; Yin, J; Hayes, M C; Catovsky, D; Gordon-Smith, E C; Hughes, J M; Goldman, J M; Galton, D
Abstract : Eight patients, five with chronic granulocytic leukaemia and three with severe aplastic anaemia, developed moderately severe airflow obstruction after allogeneic bone marrow transplantation. All eight had clinically and radiologically normal lungs before undergoing transplantation. Treatment in the patients with chronic granulocytic leukaemia before transplantation included high dose total body irradiation. All eight patients developed acute and chronic graft versus host disease after transplantation. The pulmonary syndrome consisted of cough, dyspnoea, and wheezing beginning six to 20 weeks after transplantation, with ratios of forced expiratory volume in one second (FEV1) to vital capacity (VC) falling to 60% or less of predicted values. The three patients with severe aplastic anaemia had relatively mild graft versus host disease and acute chest infection may have initiated or contributed to their airways obstruction, which subsequently resolved. The five patients with chronic granulocytic leukaemia had more severe graft versus host disease and more progressive respiratory problems; two died and three continued to have persistent airflow obstruction 11, 15, and 20 months after transplantation. None of those with chronic granulocytic leukaemia improved. Transfer factor (TLCO) was reduced in all patients after bone marrow transfer and did not improve; in the patients with chronic granulocytic leukaemia the reduction in TLCO preceded the fall in FEV1/VC ratio. Open lung biopsy in one of the patients with chronic granulocytic leukaemia showed obliterative bronchiolitis with lymphocytic infiltration consistent with graft versus host disease. Bronchodilators were of no benefit in the management of these patients, but prompt treatment of infection and early use of corticosteroids may have contributed to the improvement seen in the patients with severe aplastic anaemia.